2022
DOI: 10.3389/fpubh.2022.1010752
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal analysis of liver cancer mortality in Yunnan province, China, 2015–2019

Abstract: Liver cancer is a major public health challenge. Few published studies reported temporal trend and geographical distribution of liver cancer mortality in China, especially in less developed southwest regions with higher liver cancer incidence. In the current study, we obtained liver cancer mortality data from population-based death surveillance system in Yunnan province in 2015–2019. The mortality of liver cancer was analyzed by using the joinpoint regression model. The space distribution of liver cancer morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The A positive Moran's I value indicates that air temperatures in neighboring locations tend to have a stronger relationship than those in distant locations and vice versa. [24] [13].…”
Section: Resultsmentioning
confidence: 99%
“…The A positive Moran's I value indicates that air temperatures in neighboring locations tend to have a stronger relationship than those in distant locations and vice versa. [24] [13].…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown [15][16][17] that the disease burden of liver cancer can be spatially clustered.According to the results of global spatial autocorrelation, the DALY rate of liver cancer in 1990 was distributed randomly, and in 2017 was distributed non randomly, indicating that in recent years, the DALY rate of liver cancer at the provincial level gradually showed spatial autocorrelation and aggregation. The local spatial autocorrelation results show that in 1990, the spatial aggregation of the DALY rate of liver cancer in China was relatively concentrated at the provincial level.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the prevalence of overweight, diabetes, alcohol consumption and smoking has increased signi cantly in our country. The risk factors of liver cancer seem to be changing 4 , and the task of prevention and treatment of liver cancer still has a long way to go.. Studies have shown 5 that the disease burden of liver cancer has obvious geographical differences.. However, the current epidemiological research on liver cancer should focus on the age of onset, trend analysis and research on related risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…When the Moran's I value is less than 0, it indicates negative spatial autocorrelation. When the Moran's I value is equal to 0, it indicates a random distribution and no spatial autocorrelation 22 .…”
Section: Global Spatial Autocorrelationmentioning
confidence: 99%